Can erbium dopant occupy both cation sites in cubic barium titanate via a mechanism different than self‐compensation?. Issue 3 (18th October 2014) - Zulueta, Y. A.; Guerrero, F.; Leyet, Y.; Anglada‐Rivera, J.; González‐Romero, R. L.; Meléndez, Juan J.
<x xml:space="preserve">Abstract</x> The defect energetics for several dopant incorporation modes and the dielectric–electric properties in Er‐doped BaTiO3 were studied by numerical simulations and the dielectric modulus formalism. Two "mixed" incorporation modes, both compatible with the existence of oxygen vacancies, are proposed. Simulation results for the solution energies show that, despite self‐compensation is the most favourable mode, the mixed modes exhibit quite similar energies and, therefore, could be active under some conditions. The incorporation of Er3+ into the BaTiO3 lattice decreases the dc conductivities with respect to the undoped case at high temperatures. Molecular Dynamics calculations and experimental measurements about conducting properties of Er‐doped BaTiO3 allow one to calculate activation energies for ionic conductivity, which agree with data for oxygen migration. Experimental and Molecular Dynamics data are then correlated with the possible defect configurations. <inline-graphic xlink:href="ark:/27927/pgj984gh5h" content-type="pssb201451034-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> Scheme of the defect clusters corresponding to the proposed mixed incorporation mechanisms: (a) "Ti‐vac" and (b) "Ba‐vac". Green, grey, blue, and red balls correspond, respectively, to Ba2+, Ti4+, Er3+, and O2− ions.